Answer:
For the geometric sequence, it has two forms of formula
We are interested in the recursive formula now
{-80, 20, -5, ...}
The common ratio is (20/-80)=(-5/20)=-1/4=-0.25
So our recursive formula would bea_n=a_{n-1}*(-0.25)=a_{n-1}*(- \frac{1}{4} )an=an−1∗(−0.25)=an−1∗(−41)
Explanation:
For the geometric sequence, it has two forms of formula
{-80, 20, -5, ...}
The common ratio is (20/-80)=(-5/20)=-1/4=-0.25
So our recursive formula would be a n=a {n-1}*(-0.25)=a_{n-1}*(- \frac{1}{4} )an=an−1∗(−0.25)=an−1∗(−41)